The Influence of Principal Situational Leadership Style, Education and Training, Work Motivation on Teacher Performance - Dina Hayati; Elfrianto Elfrianto; Indra Prasetia (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
This study aims to determine the effect of situational leadership style on teacher performance at SMP Negeri 4 Pematangsiantar, (1) to determine the effect of education and training on teacher performance, (2) to determine the effect of work motivation on teacher performance, (3) to determine the effect of leadership situational, (4) education and training, work motivation on teacher performance. The sample of this study amounted to 64 respondents, namely all teachers at SMP Negeri 4 Pematangsiantar. This research uses a questionnaire distribution and the type of research with a quantitative approach by distributing questionnaires. The analytical technique used is multiple linear regression analysis and using hypothesis testing; F-test, t-test and coefficient of determination (R2). The results of this multiple linear regression research show that the results of multiple linear regression obtain the equation: Y = 2.250 + 0.632X1 + 0.388X2 + 0.475X3. The results of hypothesis testing, Ha accepted and rejected H0. The results of the t-test of situational leadership style affect teacher performance, education and training affect teacher performance and work motivation affects teacher performance X1. Meanwhile, the results of the F-test, situational leadership style, education and training and work motivation simultaneously affect teacher performance. The result of the coefficient of determination (R2) states that X1, X2, and X3 contribute 46.8% to teacher performance while the remaining 53.2% is influenced by other variables.